CLINICAL OBSERVATION OF DISCOLORING TREATMENT OF NON-VITAL TEETH BY BLEACHING - O.A. Pysarenko; Yu.I. Silenko; M.V. Khrebor (Ukrainian Medical Stomatological Academy, 2018)
A dental cosmetic is actual for everyone. Whitening of teeth can be the method of lab treatmen. Whitening facilities which are used with this goal often contain peroxide, hydrogen, carbamide peroxide, and combinations of peroxides hydrogen with sodium perborate. The treatment of 3 patients with discoloration of non-vital teeth was done. In two cases the reason of color change was the use of paste containing resorcinol-formalin. Discoloring of root of the tooth was caused by necrotic damage of the pulp. Clinically satisfactory results were received after 1-4 visits in 1-2 days. Use of the bleaching method with further aesthetic restoration of tooth crowns allows avoiding significant weakening of the tooth crown in comparison with prosthetic methods of treatment. The main whitening agent was 30-40% hydrogen peroxide in combination with sodium perborate. The positive cosmetic results were achieved in short terms. Clear compliance with of manufacturer's recommendations and the use of technology allow achieving success of treatment.